The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1073/pnas.78.3.1675
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, culture, and immunocytochemical characterization of epididymal epithelial cells from pubertal and adult rats.

Abstract: A method for the isolation and culture of epididymal e ithelial cells obtained from pubertal and old adult rats is d red. This method permits the establishment of primary cultures of these cells in monolayers from aggregates isolated from whole epididymides and major epididymal anatomical segments (caput, corpus, and cauda) after trypsin and collagenase digestions. A large number of cultured epididymal cells retain a differentiated function as demonstrated by the immunocytochemical and radioimmunoassay finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

1983
1983
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 35 publications
1
31
0
1
Order By: Relevance
“…Epididymal epithelial cells were isolated from 5-week-old Sprague-Dawley rats (Saitama Experimental Animal Supply Co. Ltd, Saitama, Japan) according to the method reported previously (Kierszenbaum et al 1981, Leung et al 2001. To minimize contamination of non-epithelial cells and inhibition of attachment of epithelial cells to culture dishes by spermatozoa, we used immature rats, which do not contain spermatozoa (Kierszenbaum et al 1981, Leung et al 2001.…”
Section: Preparation and Primary Culture Of Rat Epididymal Epithelialmentioning
confidence: 99%
See 2 more Smart Citations
“…Epididymal epithelial cells were isolated from 5-week-old Sprague-Dawley rats (Saitama Experimental Animal Supply Co. Ltd, Saitama, Japan) according to the method reported previously (Kierszenbaum et al 1981, Leung et al 2001. To minimize contamination of non-epithelial cells and inhibition of attachment of epithelial cells to culture dishes by spermatozoa, we used immature rats, which do not contain spermatozoa (Kierszenbaum et al 1981, Leung et al 2001.…”
Section: Preparation and Primary Culture Of Rat Epididymal Epithelialmentioning
confidence: 99%
“…To minimize contamination of non-epithelial cells and inhibition of attachment of epithelial cells to culture dishes by spermatozoa, we used immature rats, which do not contain spermatozoa (Kierszenbaum et al 1981, Leung et al 2001. Briefly, epididymides were dissected out and minced into small fragments.…”
Section: Preparation and Primary Culture Of Rat Epididymal Epithelialmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the cellular organization of an epithelium plays an integral part in its function, an important consideration in our culturing of the epididymal epithelium was to avoid procedures which initially reduce the tissue to a single cell suspension, as have been described elsewhere (Kierszenbaum et al, 1981;Klinefelter et al, 1982;Joshi, 1985). It may be argued that culture of intact lengths of epididymal tubules (Orgebin-Crist & Jahad, 1979) could prevent spermatozoa being exposed to a potentially activating environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts to culture epididymal principal cells in vitro have shown that normal morphological features and some biochemical function (e.g. steroid synthesis) can be maintained for several days (Kierszenbaum et al, 1981;Klinefelter et al, 1982;Joshi, 1985). Furthermore, the organ culture of epididymal tubules, in which morphological integrity of epithelium remains largely intact, will induce some degree of sperm maturation (Orgebin-Crist & Jahad, 1979;Cuasnicu et al, 1984), but this culture methods allows only limited access to the tubule lumen.…”
Section: Introductionmentioning
confidence: 99%